Relasi Kekerabatan Patronase Masyarakat Muna - Asliah Zainal; Muhammad Asrianto Zainal; Waode Ainul Rafiah; Wa Kina Wa Kina (Institut Agama Islam Negeri Kendari, 2021)
This study is addressed to two things: the relationship of kinship and patronage, which take place in social aspect (education and economy) and culture (life cycle ceremony), and the relation of patronage kinship system, which implies on cohesion social community of Muna. This study showed that the relation of the Muna family was tied socially and culturally by two vertices, descent/affinity relation and patronage relation or patronage kinship system and in local term called intaidi bhasitie (we are family). The patronage kinship in Muna family works in almost every aspect of community life, both in social; educational, economic, even political; and cultural (life cycle ceremony). By using Anthropological family, this study argues that the kinship systems wrapped by patronage or boosted patronage by kinship relationships are neither firm nor sustainable. It may be safe in education, economy, and cultural aspects but may be weakened in political preference. Even though a relative still tied up in a family's node but his indifference will be called